Technology in sport: Medical and ethical repercussions - Mountjoy, M.; Gordon, I.; McKeown, J.; Constantini, N. (Clinical Journal of Sport Medicine, 2009)
The author reflects on the medical and ethical repercussion of technological innovations in sports. It cites the technological swimming saga, which continued throughout 2008 and the designs of swimsuit model which are believed to fit the body like a second skin and to increase buoyancy. The author stresses that the most difficult part of the suit to apply is that which stretches over the lower limbs resulting to the incidence of purpuric lesions and ecchymoses among athletes.